The Role of the God Nergal in Life Political ,Economic ,Social lite and Astronomy - AL-Mashhadani, Sabah Jassim Homadey; Kadhim, Haifa Fadel (Al-Adab Journal, 2020)
The epics and legends in all the civilizations of the East and all the gods of the underworld and its dominion, which is originally a solar garden have a role in maintaining the balance between the upper and lower worlds, which represents the sun in the middle of the day in the hot summer also characterized as God’s agriculture and justice and the fighting force and it is at the same time the god Nergal is the Sumerian god and the god of the lower world, as well as being among the gods of epidemics, diseases and bloody battles, as well as of the field goddess Mars in the Babylonian and Assyrian astrologers. The worship of God Nergal has taken special care since the uncle T until late Sumerian periods until after the birth of Christ as mentioned in the writings of God Nergal Palmyra and the writings of the urban form and spread Nrjul worship to the West.